REMOTE CONTROL EXPERIMENTS IN CHEMICAL ENGINEERING EDUCATION - A.M. Josceanu; P. Postelnicescu; A.M. Dumitrescu; V. Plesu; C. Stefan (Chemical Engineering Transactions, 2009)
Abstract preview not available - see full-text PDF article.